Thermal and acoustic performance of additive aerogel-clay bricks. Issue 1 (1st December 2022) - Buratti, C; Merli, F; Belloni, E; Spaccini, F
Abstract: Aerogel is a nano-porous material with significant thermal insulation properties and a good candidate for improving the performance of traditional materials for energy efficiency in buildings. It is therefore gaining more and more interest in the construction industry and researchers are carrying out investigations for incorporating granular aerogel into bricks. The aim of the present paper is the experimental investigation of the influence on both thermal and acoustic properties of granular aerogel in mixed clay-aerogel bricks. Samples with 5% of granular aerogel were tested and compared with the pure clay. For each type of brick, the thermal conductivity (λ) was evaluated in a Small Hot Box apparatus. The acoustic performance (absorption coefficient α and Transmission Loss TL) was measured at normal incidence in a traditional impedance tube. The results reveal that the thermal conductivity of clay sample with 5% of aerogel in the initial mixture decrease to 0.212 W/(mK) at 10°C, in comparison with 0.310 W/(mK). Also α-values better than the ones without aerogel were achieved (α = 0.29 at about 1600 Hz instead of 0.11) whereas TL values, despite good (24 - 34 dB depending on the frequency), are lower than the ones obtained for the pure clay samples, due to the lower density, according to the Mass Law.